Analysis of Product Quality, Brand Image, and Brand Ambassador Influence on Purchasing Decisions for Nivea Products in Klaten Regency - Muh. Farhan Ali Harazim; Ida Aryati; Raisa Aribatul Hamidah (GoodWill, 2026)
This study examines the effects of product quality, brand image, and brand ambassador on purchasing decisions for NIVEA products in Klaten Regency, Indonesia. The increasing competition in the skincare industry has encouraged companies to strengthen product attributes and marketing communication strategies to influence consumer behavior. A quantitative research design with a causal associative approach was employed. Data were collected through a structured questionnaire distributed to 100 consumers who had purchased NIVEA products, selected using purposive sampling based on predetermined criteria. The collected data were analyzed using multiple linear regression with the assistance of IBM SPSS software. The findings reveal that product quality, brand image, and brand ambassador each have a positive and statistically significant effect on purchasing decisions, both partially and simultaneously. Product quality and brand image demonstrate the strongest influence, indicating that consumers prioritize functional benefits, safety, and brand credibility when making purchasing decisions. Brand ambassadors also contribute positively, although with a relatively smaller effect, by enhancing brand attractiveness and trust through public figure representation. The coefficient of determination (Adjusted R²) of 0.795 indicates that 79.5% of purchasing decision variance can be explained by the three independent variables, while the remaining 20.5% is influenced by other factors beyond the research model. These results highlight the importance of integrating product excellence, strong brand image, and effective brand ambassadors in developing competitive marketing strategies. The study provides managerial implications for skincare companies in strengthening consumer trust and purchasing decisions, particularly in highly competitive local markets.